Cognitive Restructuring Before Versus After Exposure: Effect on Expectancy and Outcome in Individuals With Claustrophobia. Issue 6 (November 2022) - Krause, Kirstyn L.; Koerner, Naomi; Antony, Martin M.
Maximizing the discrepancy between expected and actual outcomes during exposure (i.e., expectancy violation) is thought to optimize inhibitory learning. The current study examined Craske et al.'s suggestion that engaging in cognitive restructuring (CR) before exposure prematurely reduces expectancy and mitigates outcomes. Participants ( N = 93) with claustrophobia were randomly assigned to either 15 minutes of CR before exposure ( CR Before ) or 15 minutes of CR after exposure ( CR After ). Although the CR Before condition experienced greater expectancy reduction before exposure than the CR After condition, both groups experienced similar overall expectancy reduction by the end of the intervention. Groups experienced similar gains, with large significant improvement at posttreatment and follow-up. Results suggest that both cognitive therapy and exposure therapy lead to expectancy reduction, but that the order of these interventions does not impact outcome. Clinicaltrials.org registration #NCT03628105.